Unilateral nephrectomy versus renal arterial embolization and technique survival in peritoneal dialysis patients with autosomal dominant polycystic kidney disease. Issue 2 (20th November 2019) - Pierre, Malika; Moreau, Karine; Braconnier, Antoine; Kanagaratnam, Lukshe; Lessore De Sainte Foy, Célia; Sigogne, Mikael; Béchade, Clémence; Petrache, Andréea; Verger, Christian; Frimat, Luc; Duval-Sabatier, Ariane; Caillard, Sophie; et al.
Abstract: Background: Autosomal dominant polycystic kidney disease (ADPKD) is a common genetic disorder associated with progressive enlargement of the kidneys and liver. ADPKD patients may require renal volume reduction, especially before renal transplantation. The standard treatment is unilateral nephrectomy. However, surgery incurs a risk of blood transfusion and alloimmunization. Furthermore, when patients are treated with peritoneal dialysis (PD), surgery is associated with an increased risk of temporary or definitive switch to haemodialysis (HD). Unilateral renal arterial embolization can be used as an alternative approach to nephrectomy. Methods: We performed a multicentre retrospective study to compare the technique of survival of PD after transcatheter renal artery embolization with that of nephrectomy in an ADPKD population. We included ADPKD patients treated with PD submitted to renal volume reduction by either surgery or arterial embolization. Secondary objectives were to compare the frequency and duration of a temporary switch to HD in both groups and the impact of the procedure on PD adequacy parameters. Results: More than 700 patient files from 12 centres were screened. Only 37 patients met the inclusion criteria (i.e. treated with PD at the time of renal volume reduction) and were included in the study (21 embolized and 16 nephrectomized). Permanent switch to HD was observed in 6 embolized patients (28.6%) versus 11 nephrectomized patients (68.8%) (P = 0.0001). Renal artery embolization was associated with better technique survival: subdistribution hazard ratio (SHR) 0.29 [95% confidence interval (CI) 0.12–0.75; P = 0.01]. By multivariate analysis, renal volume reduction by embolization and male gender were associated with a decreased risk of switching to HD. After embolization, a decrease in PD adequacy parameters was observed but no embolized patients required temporary HD; the duration of hospitalization was significantly lower [5 days [interquartile range (IQR) 4.0–6.0] in the embolization group versus 8.5 days (IQR 6.0–11.0) in the surgery group. Conclusions: Transcatheter renal artery embolization yields better technique survival of PD in ADPKD patients requiring renal volume reduction.